Development of the upgraded single crystal dispersion interferometer (SCDI-U) and its first measurements of the line integrated electron densities in KSTAR during shattered pellet injections - Lee, D; Lee, KC; Juhn, J; Lee, J; Kim, J; Park, S; Lehnen, M; Park, Y; Jeong, J; Yim, J; Ghim, Y (IOP Publishing, 2023)
Dispersion interferometers (DI) are widely used to measure line integrated electron densities in many fusion devices. A recent development of a heterodyne single crystal DI (SCDI) with a laser wavelength of 1064 nm (Lee et al 2021 Rev. Sci. Instrum. 92 033536) allows an easier and simpler optical setup by using only one, instead of two, nonlinear crystal. It is found that the reported heterodyne SCDI with an acoustic-optical modulator (AOM) has different beam paths between the frequency-shifted, via the AOM, fundamental and second harmonics which act as the reference beams. Such a separation of the reference beams inevitably produces non-removable phase shifts associated with mechanical vibrations, resulting in a reduction of the removing efficiency of the mechanical vibrations that DI systems can provide. By utilizing the fact that the diffraction angle due to the AOM is inversely proportional to the frequency of the laser beam and linearly proportional to an order of the frequency-shift, the SCDI-Upgrade (SCDI-U), which has complete overlap of the optical paths for both probing and reference beams from the laser source to the detectors, is proposed in this work. Its first measurements in KSTAR during shattered pellet injections are reported, and results obtained by the SCDI-U are compared with those from the existing two-color interferometer (TCI) in KSTAR. It is found that the SCDI-U measures the electron density more reliably during such an abrupt and large density change than the TCI does. Qualitative analyses on the effects of different injection schemes of the shattered pellets and possible application of the SCDI-U for ITER are also discussed.